The dynamic models of perception vocabulary (based on the Ukrainian, Polish, and English languages) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article describes dynamic models of perception vocabulary in the Ukrainian, Polish, and English languages in the form of a construal that realizes the derivational type of a situation – the type of source derivational potential and target derivational implication of state of affairs correlations. The derivational type of a situation is viewed in the aspect of a certain type of semantic relations, indicating the modification of the source and target state of affairs predicate-actant structures based on the perception situation participantsʼ role, communicative, taxonomic, referential and deictic characteristics exchanges.
Keywords: dynamic model; semantic derivation; perception vocabulary; actant (participant); semantic relations; the source situation; the target situation